Current plate velocities relative to hotspots: implications for hotspot motion, mantle viscosity and global reference frame - Wang, SM; Wang, R (Earth and Planetary Science Letters, 2001)
The HS2-NUVEL1 model being used for current plate velocities relative to hotspots is shown to be generally inconsistent with the observed hotspot data sampled from non-Pacific regions. Instead, we determine the T22A model, which provides a good and consistent fit to the trends of globally distributed hotspot traces, but predicts plate velocities at hotspots systematically lower than the observed rates of hotspot volcanic migrations. As a result, it implies that the return flow in the lower mantle has a velocity about 1/4 of the plate velocity, and that the lower mantle is about 20 times more viscous than the upper mantle. Although hotspots are not relatively fixed, they do define a global reference frame for plate motion and mantle convection. (C) 2001 Elsevier Science B.V. All rights reserved. Geochemistry & Geophysics SCI(E) 22 ARTICLE 3-4 133-140 189